2013
DOI: 10.4236/ojts.2013.33019
|View full text |Cite
|
Sign up to set email alerts
|

Diaphragmatic Plication: Retrospective Study with 54 Patients

Abstract: Objective: This study seeks to evaluate the results of surgery performed according to the etiological causes of diaphragmatic eventration or paralysis. Method: Files of 54 patients (35 males, 19 females; mean age: 39.1 ± 3.01 years) who had undergone diaphragm plication between January 2005 and June 2011 in two clinics located in Istanbul were studied in terms of pulmonary spirometry, applied surgical procedure, duration of hospitalization, morbidity, and mortality. Results: In diaphragm plications, observed e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Consensus was reached about performing early plication for diaphragmatic paralysis in infants and young children [ 5 ]. Çelik et al suggested that early and timely plication for diaphragmatic paralysis improves functional status and shortens the length of hospitalization [ 6 ]. However, the timing of surgical plication remains controversial in adults.…”
Section: Discussionmentioning
confidence: 99%
“…Consensus was reached about performing early plication for diaphragmatic paralysis in infants and young children [ 5 ]. Çelik et al suggested that early and timely plication for diaphragmatic paralysis improves functional status and shortens the length of hospitalization [ 6 ]. However, the timing of surgical plication remains controversial in adults.…”
Section: Discussionmentioning
confidence: 99%